Determining the Location of Nenas Processing Factories in North Sumatra Using Dijkstra Algorithm - Siringoringo, Yan Batara Putra; Sitinjak, Lentina; Tarigan, Enita Dewi (Journal of Research in Mathematics Trends and Technology, 2024)
Pineapples have many health advantages. In addition to having many health benefits, this fruit can be processed into juice, jam, syrup, and chips. Pineapple is often eaten as fresh fruit and utilized primarily for its flesh. The community has not utilized this potential to its fullest extent. The production of pineapples is ranked second after oranges, according to statistics from the Central Statistics Agency of the North Sumatra Province for the year 2018-2019. This indicates that pineapples have a lot of potential for development both domestically and eventually for export. Determining the best route for transportation to the pineapple processing factory and the lack of one in North Sumatra provide the primary research challenges. In literary works, the factory’s location is ascertained by analyzing production levels and utilizing Dijkstra algorithm programming to find the shortest transit path from the producing region to the factory. Using Google Maps, the 10 highest generating regions were identified for this study, with the district capital serving as the vertex and the distance between regions serving as the edge. According to the research findings, the pineapple processing plant was located in the middle of North Tapanuli Regency, and the shortest path between each region and the processing factory location was identified